Redes de atores e o seu papel no desenvolvimento de corredores: Diagnóstico e proposta de governança para o corredor rodoviário bioceânico Mato Grosso do Sul - Portos do norte do Chile - Ledys de Franco; Julia Souza Borba Gonçalves; Miguel Atienza; Pedro Silva Barros (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This study addresses a key challenge: to analyze the current coordination of the Bioceanic Road Corridor initiative to promote infrastructure integration and cooperation between the State of Mato Grosso do Sul, the Paraguayan Chaco, the NOA regions of Argentina and the ports of northern Chile by examining the network of stakeholders. This analysis is fundamental to rethink the form of governance that can guide this initiative in the future towards the achievement of the declared objectives. The purpose of this document is to explain how the corridor's network of stakeholders is organized and to propose a possible form of governance that would allow a better coordination among the participating stakeholders, so that the corridor can become an instrument for regional development.
Keywords: O18; H54; C31; 330; Bioceanic Road Corridor; infrastructure integration; South America; development corridors